Assessment of the Drug Interaction Potential of Unconjugated and GalNAc3-Conjugated 2'-MOE-ASOs - Colby S. Shemesh; Rosie Z. Yu; Mark S. Warren; Michael Liu; Mirza Jahic; Brandon Nichols; Noah Post; Song Lin; Daniel A. Norris; Eunju Hurh; Jane Huang; Tanya Watanabe; et al. (Elsevier, 2017)
Antisense oligonucleotides are metabolized by nucleases and drug interactions with small drug molecules at either the cytochrome P450 (CYP) enzyme or transporter levels have not been observed to date. Herein, a comprehensive in vitro assessment of the drug-drug interaction (DDI) potential was carried out with four 2'-O-(2-methoxyethyl)-modified antisense oligonucleotides (2'-MOE-ASOs), including a single triantennary N-acetyl galactosamine (GalNAc3)-conjugated ASO. Several investigations to describe the DDI potential of a 2'-MOE-ASO conjugated to a high-affinity ligand for hepatocyte-specific asialoglycoprotein receptors are explored. The inhibition on CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4 and induction on CYP1A2, CYP2B6, and CYP3A4 were investigated in cryopreserved hepatocytes using up to 100 μM of each ASO. No significant inhibition (half maximal inhibitory concentration [IC50] > 100 μM) or induction was observed based on either enzymatic phenotype or mRNA levels. In addition, transporter interaction studies were conducted with nine major transporters per recommendations from regulatory guidances and included three hepatic uptake transporters, organic cation transporter 1 (OCT1), organic anion transporting polypeptide 1B1 (OATP1B1), and OATP1B3; three renal uptake transporters, organic anion transporter 1 (OAT1), OAT3, and OCT2; and three efflux transporters, P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), and bile salt export pump (BSEP). None of the four ASOs (10 μM) were substrates of any of the nine transporters, with uptake <2-fold compared to controls, and efflux ratios were below 2.0 for BCRP and P-gp. Additionally, neither of the four ASOs showed meaningful inhibition on any of the nine transporters tested, with the mean percent inhibition ranging from −38.3% to 24.2% with 100 μM ASO. Based on these findings, the unconjugated and GalNAc3-conjugated 2'-MOE-ASOs would have no or minimal DDI with small drug molecules via any major CYP enzyme or drug transporters at clinically relevant exposures.